2017
DOI: 10.1080/00222895.2017.1375454
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Movement and Gait Quality Characteristics in Pre-School Children

Abstract: There is a dearth of suitable metrics capable of objectively quantifying motor competence. Further, objective movement quality characteristics during free play have not been investigated in pre-school children. The aims of this study were to characterize children's free play physical activity and investigate how gait quality characteristics cluster with free play in pre-school children (3-5 years old). Sixty-one children (39 boys; 4.3 ± 0.7 years, 1.04 ± 0.05 m, 17.8 ± 3.2 kg) completed the movement assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 72 publications
2
13
0
Order By: Relevance
“…Despite the mounting evidence for the benefit of qualifying contextual MC or movement quality data, there remains an over-predominance in focusing on the quantity of activity, rather than the quality [9,10]. Only recently has there been a trend towards a joint consideration of exercise quantity and quality [9][10][11][12][13][14]. A pivotal meta-analysis highlighted that PA interventions dedicated to improving quantity of PA report little effect [15].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the mounting evidence for the benefit of qualifying contextual MC or movement quality data, there remains an over-predominance in focusing on the quantity of activity, rather than the quality [9,10]. Only recently has there been a trend towards a joint consideration of exercise quantity and quality [9][10][11][12][13][14]. A pivotal meta-analysis highlighted that PA interventions dedicated to improving quantity of PA report little effect [15].…”
Section: Introductionmentioning
confidence: 99%
“…This research aims to analyze the constructs mentioned in the previous paragraphs, due to the importance of these factors in the psychosocial health of school children. These subjects in school-age children have certain characteristics that distinguish them from those in adolescents and adults, due to a change from childhood to preadolescence occurring at this age [25]. During this stage, the physical development of school children has reached maturity and harmony, preparing the body for the pubertal developments characteristic of adolescence [26].…”
Section: Introductionmentioning
confidence: 99%
“…Although empirical and conceptual evidence exists to support the reciprocal relationship between motor competence and PA (Stodden et al, 2008), there is a limited evident base of motor competence related to PA measurement in pre-school children, largely due to the complexity in examining such constructs in this age group (Adamo et al, 2016;Goldfield, Harvey, Grattan, & Adamo, 2012). When studies have investigated PA and motor competence they tend to examine this as a relationship, where large variability in not only motor competence, but also PA, is reported, which can conceivably mask, or indeed create spurious, responses or relationships (Adamo et al, 2016;Clark, Barnes, Swindell, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a novel metric, spectral purity, has been proposed as a viable measure of movement and gait quality, where the purity of the fundamental frequency spectra (signal) during movement, specifically relating to gait, is quantified (Clark, 2017). Interestingly, in Clark et al (2017), it was suggested that spectral purity may be a viable proxy for motor competence, assessed using MABC2, and movement quality in pre-school children.…”
Section: Introductionmentioning
confidence: 99%